PENGARUH SERVANT LEADERSHIP, DISIPLIN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA GURU SD NEGERI DI WILAYAH PEUSANGAN KABUPATEN BIREUEN - Safwandi, Safwandi; Konadi, Win (LPPM-UNIKI, 2023)
This study aims to determine the effect of Servant Leadership, Teacher Work Discipline and Job Satisfaction both partially and simultaneously on teacher performance. The research was in the form of a survey of a sample of 226 public elementary school teachers in the Peusangan area of ​​Bireuen Regency. This type of quantitative research was carried out using descriptive and associative analysis, with a path analysis model approach. The results of the path analysis show, 1) the Servant Leadership factor has a direct effect of 0.472 on teacher performance, 2) the teacher discipline factor has a direct effect of 0.312 on teacher performance, 3) the job satisfaction factor has a direct effect of 0.214 on teacher performance, 4) The servant leadership factor through discipline and teacher job satisfaction have an effect of 46.75% on teacher performance, 5) Work discipline factors through servant leadership and job satisfaction have an effect of 32.6% on teacher performance, 6). The Job Satisfaction Factor through Servant Leadership and Work Discipline influences Teacher Performance by 26.56%. 7) Simultaneously servant leadership, work discipline and job satisfaction contribute to changes in teacher performance by 57.9%. While the remaining 42.1% is influenced by other factors not examined, researchers suspect from the aspects of work motivation, teacher competence, work environment and others.